Analysis of Prototype Electric Car Chassis Construction using Aluminum Hollow 6061 Profiles using Inventor Software 2016: Analisis Bentuk Kontruksi Chassis Mobil Listrik Prototype Tipe Hollow Alumunium 6061 Menggunakan Software Inventor 2016 - Muhammad Zahir Bahasyim; Riyan Ariyansah; Oktarina Heriyani (Fakultas Teknik Universitas Pancasila, 2023)
Vehicles are a means of transportation. Most vehicles use fossil fuels as an energy source. Fossil fuels will run out, so electricity is used as a substitute. Electric fuel is environmentally friendly and does not emit pollution. Making a prototype electric car, one of which is preparing a design and simulating it using software. This study aims to find the best 6061 hollow aluminum chassis model through static analysis using Autodesk Inventor software with the finite element analysis (FEA) method. This study compares three chassis models, namely chassis patterns H, X, and Y, which will be subjected to a static load test of 900 N, including the driver's load of 600 N. The values obtained are von Mises stress, displacement, and the safety factor. The dimensions of the chassis are 2,160 mm by 750 mm by 500 mm, with a thickness of 2 mm. The results can be concluded: the H-pattern chassis is the best and easier to design compared to the X and Y chassis. This chassis has a von Mises stress value of 84.47 MPa, a displacement value of 0.89 mm, and a safety factor of 3.20. Based on these results, the model H chassis is safe.